Bayān Athar Istikhdām Numūdhaj al-Ta‘allum al-Tawlīdī fī Tanmīyat al-Mafāhīm al-Naḥwīyah li-Muta‘allimī al-Lughah al-‘Arabīyah al-Nāṭiqīna bi-Ghayrihā - Anas ibn Hosen Al Ali (Al-Ma‘rifah, 2019)
The importance of research is to help teachers to know the grammatical concepts related to the nominatives and accusative cases suitable for students of advanced level in the Institute of Arabic Language Teaching for Non-native Speakers at the Islamic University of Madinah. Other than that to contribute to the knowledge of the impact of the use of the model of learning in the development of grammatical concepts related to the nominatives and accusative cases. Also, to help teachers using the generative learning model for students of non-natives speaker and curriculum developers those involved by the generative model learning. This research aims to identify the problem of difficulty faced by non-native speaker students to acquire the Arabic grammar concept due to the rigidity of grammatical rules. The research also used a semi-experimental method, and the research reached the results to construct a list of grammatical concepts related to the nominatives and accusative cases suitable for students of advanced level, and it is effective on the using the generative learning model to develop Arabic grammatical concepts.